Program pemberdayaan masyarakat dalam mendukung kesejahteraan masyarakat di Kampung Inya Distrik Manokwari Utara Kabupaten Manokwari: Community empowerment program in supporting community welfare in Inya Village North Manokwari District Manokwari Regency - Lukas Y. Sonbait; Nurhaidah I. Sinaga; Ikram Karim; Novena Silubun; Apner Sabloit; Yustina L. D. Wambrauw (Fakultas Peternakan Universitas Papua, 2023)
ABSTRACT The implementation of the empowerment program was carried out in Inya village, North Manokwari District, Manokwari Regency. The expected output is the community's understanding of the potential possessed in the village which has an impact on changing behavior and improving community health and education. In implementing it, the team together with the community looked at the village strategic plan and budget that could be used for synergy between IDM and RPJMkam. There are several activities carried out in the fields of education, health and socio-culture as well as developing the entrepreneurial spirit of the community. The people of Inya Village were very enthusiastic about participating in the program, both in theory and in field practice. The development of village PUSTU is one of the efforts to improve the health status of the community. Beach processing efforts for tourist areas are part of utilizing village potential to support the welfare of the village community. Keywords: Community welfare; Inya village; Social services ABSTRAK Pelaksanaan program pemberdayaan dilaksanakan di Kampung Inya, Distrik Manokwari Utara, Kabupaten Manokwari. Luaran yang diharapkan adalah terjadinya pemahaman masyarakat terhadap potensi yang dimiliki di kampung yang berdampak pada perubahan perilaku dan peningkatan kesehatan dan pendidikan masyarakat. Dalam pelaksaanannya tim bersama masyarakat bersama-sama melihat renstra dan anggaran kampung yang dapat digunakan untuk sinergi antara IDM dan RPJMkam. Ada beberapa kegiatan yang dilakukan dalam kegiatan baik dibidang Pendidikan, kesehatan dan sosial budaya serta mengembangkan jiwa wirausaha masyarakat. Masyarakat kampung Inya sangat antusias mengikuti program baik teori maupun praktek lapangan. Pembangunan PUSTU kampung merupakan salah satu upaya untuk meningkatkan status kesehatan masyarakat. Upaya pengolahan pantai untuk kawasan wisata adalah bagian dari memanfaatkan potensi kampung untuk pendukung kesejahteraan masyarakat kampung. Kata kunci: Kampung Inya; Kesejahteraan masyarakat; Layanan sosial